2023
DOI: 10.7554/elife.83469
|View full text |Cite
|
Sign up to set email alerts
|

Protein feeding mediates sex pheromone biosynthesis in an insect

Abstract: Protein feeding is critical for male reproductive success in many insect species. However, how protein affects the reproduction remains largely unknown. Using Bactrocera dorsalis as the study model, we investigated how protein feeding regulated sex pheromone synthesis. We show that protein ingestion is essential for sex pheromone synthesis in male. While protein feeding or deprivation did not affect Bacillus abundance, transcriptome analysis revealed that sarcosine dehydrogenase (Sardh) in protein-fed males re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…In B. dorsalis, proteins can be converted into precursors for sex pheromone synthesis; therefore, a protein deficiency can affect this process. 100 This was also observed in Ceratitis capitata and B. tryoni, where the amount of protein intake is directly related to the intensity of sex pheromone release. 226,227 Protein intake also makes A. obliqua more sensitive to sex pheromones.…”
Section: Effects Of External Factors On Reproductionmentioning
confidence: 69%
See 3 more Smart Citations
“…In B. dorsalis, proteins can be converted into precursors for sex pheromone synthesis; therefore, a protein deficiency can affect this process. 100 This was also observed in Ceratitis capitata and B. tryoni, where the amount of protein intake is directly related to the intensity of sex pheromone release. 226,227 Protein intake also makes A. obliqua more sensitive to sex pheromones.…”
Section: Effects Of External Factors On Reproductionmentioning
confidence: 69%
“…33 Further studies have shown that both are synthesized in the rectum by Bacillus using glucose, threonine, and glycine as substrates. 99,100 Based on studies of Zhang et al, 101 and Gui et al, 100 the TMP and TTMP synthesis pathway in the B. dorsalis rectum is proposed (Fig. 1).…”
Section: Olfactory Signals: Sex Pheromonesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, some amino acid metabolic pathways that regulate insect reproduction were also found to be significantly enriched. Recent studies indicate that phenylalanine metabolism regulates reproduction and mating behavior in flies and mosquitos (Proline et al, 2014;Arya et al, 2021), while glycine, serine, and threonine metabolism are involved in sex pheromone biosynthesis in the oriental fruit fly (Gui et al, 2023). Overall, when A. corpulenta beetles were subjected to LCP light stress, not only was the expression of insect environmental signaling pathway-related genes affected, but that of amino acid metabolism pathways related to insect reproduction was also affected.…”
Section: Discussionmentioning
confidence: 99%